Familism and the Far Right: Unveiling the Strong Families Programme - Horst, Claudio Henrique Miranda; Alves, Luísa Duarte Torres (Argumentum, 2024)
This article analyses the ideological direction, under the Bolsonaro government, of the Ministry of Women, Family and Human Rights’ “Strong Families Programme”. This is documentary research, employing dialectical historical materialism, with a qualitative emphasis. The data was analysed using the content analysis technique. The results demonstrate a facet of neoconservative familism, by focusing only on socio-emotional training (strengthening bonds) as a strategy and solution for the expressions of the “social question”, together with the refusal to offer public and state social protection.